2015
DOI: 10.18632/oncotarget.6572
|View full text |Cite
|
Sign up to set email alerts
|

Artemin is hypoxia responsive and promotes oncogenicity and increased tumor initiating capacity in hepatocellular carcinoma

Abstract: Hypoxia has been reported to regulate the cancer stem cell (CSC) population yet the underlying mechanism is poorly characterized. Herein, we show that Artemin (ARTN), a member of the glial cell derived neurotrophic factor family of ligands, is a hypoxia-responsive factor and is essential for hypoxia-induced CSC expansion in hepatocellular carcinoma (HCC). Clinically, elevated expression of ARTN in HCC was associated with larger tumor size, faster relapse and shorter survival. In vitro, HCC cells with forced ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…It has been reported that macrophages can be recruited into HCC tissue by SEMA3A, and overexpression of SEMA3A indicates poor prognosis in hepatocellular carcinoma . Artemin was shown to be related to early relapse, shortened overall survival and large tumor size . The involvement of all the above mentioned genes indicates that immune processes contribute to tumor development and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that macrophages can be recruited into HCC tissue by SEMA3A, and overexpression of SEMA3A indicates poor prognosis in hepatocellular carcinoma . Artemin was shown to be related to early relapse, shortened overall survival and large tumor size . The involvement of all the above mentioned genes indicates that immune processes contribute to tumor development and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Artemin promotes the metastatic properties and tumor-initiating capacity of HCC by AKT modulation of factors involved in EMT and stemness [83]. Chronic hepatitis C virus (HCV) infection, an important factor in the etiology of HCC, is also associated with EMT and CSC pathways.…”
Section: Emt Phenotype Is Linked With the Biology Of Csc In Hccmentioning
confidence: 99%
“…A recent study suggested that during hypoxia, HIF-1α upregulated Artemin expression and this in turn promoted CSC and EMT functions in HCC [83]. Won et al demonstrated that hypoxia could trigger Stat3-mediated CD133 upregulation with concomitant enhanced HIF-1α levels [96].…”
Section: Emt Phenotype Is Linked With the Biology Of Csc In Hccmentioning
confidence: 99%
“…Over the past few years, pro-tumor functions of artemin have gain prominence. 8,9 In this study, authors provide robust evidence that artemin promotes HCC progression and could be a potential therapeutic target. More importantly, it is noteworthy that artemin production is predominantly regulated by an erythroid lineage subset, namely Ter-cells.…”
mentioning
confidence: 86%